Warunki perspektywy zrównoważonego rozwoju miast - Słodczyk, Janusz (Conditions and prospects for sustainable urban development, 2007)
The aim of this article is to identify the areas which are most important for urban sustainable development. It is tried to define the spatial form of cities which is sustainable by comparing spatially compact and dispersed cities. It is argued that concentrated urban arrangements are more sustainable than other types of spatial arrangements. A fundamental issue is sustainable urban transport. The proposed directions of development concem new technological Solutions, as well as limiting the need for transport. Other issues indicated in the article are construction design, access to water and water use, waste management and the deveIopment of the urban ecosystem. In the finał part of the article, different models of the relation between cities and their surrounding areas are analyzed. One conclusion is that achieving sustainable urban development requires a comprehensive approach, in which the surrounding areas should be included.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 237-247